2011
DOI: 10.4166/kjg.2011.57.1.42
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Liver Abscess Caused byFusobacterium nucleatumin a Patient with Recurrent Periodontal Diseases

Abstract: Fusobacteria are anaerobic gram-negative, non-spore forming bacilli found in normal flora of the oral cavity, urogenital tract, and gastrointestinal tract. Fusobacterium nucleatum has been seldom reported as a cause of liver abscess, particularly in immunocompetent hosts. A 55-year-old man with frequent periodontal disease visited our hospital with intermittent fever and headache for 2 months. Abdominal CT scan revealed an 8.2×6 cm mass in the right hepatic lobe with central low density. Abscess culture reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is one of the most common oral species isolated from extra-oral infections such as blood, brain, lung, liver, joints, abdominal, obstetrical and gynaecological infections and abscesses. It has recently been reported as a cause of liver abscess in a patient suffering from recurrent periodontal disease [4]. We report the first case of F. nucleatum pyogenic liver abscess as the initial presentation of a rectosigmoid carcinoma.…”
Section: Introductionmentioning
confidence: 93%
“…It is one of the most common oral species isolated from extra-oral infections such as blood, brain, lung, liver, joints, abdominal, obstetrical and gynaecological infections and abscesses. It has recently been reported as a cause of liver abscess in a patient suffering from recurrent periodontal disease [4]. We report the first case of F. nucleatum pyogenic liver abscess as the initial presentation of a rectosigmoid carcinoma.…”
Section: Introductionmentioning
confidence: 93%
“…It is one of the most common oral species isolated from extra‐oral infections, such as blood, brain, lung, liver, joints, abdominal, obstetrical and gynecological infections and abscesses. Recent reports reveal that this bacterium causes liver abscess in patients suffering from recurrent periodontal disease . Enterococcus faecalis is a Gram‐positive pathogenic bacteria usually found in the tooth caries of patients that survives and grows within the dentinal tubules and reinfects an obturated root canal.…”
Section: Introductionmentioning
confidence: 99%
“…Several periodontopathic bacterial species in the PLA were identified, including Fusobacterium nucleatum, Treponema denticola, Prevotella intermedia and Porphyromonas gingivalis [9]. Another case reported that Fusobacterium nucleatum was the etiologic agent for LPA in an immunocompetent patient with periodontal disease [10].…”
Section: Review Systemic Complication From Oral Bacterial Infectionmentioning
confidence: 99%
“…Other complications, such as brain and liver pyogenic abscess, have also been related to oral infections [8][9][10][11]. Although approximately 50% of pyogenic liver abscess (PLA) cases are considered as cryptogenic, PLA formation is generally attributed to the transmission of infection via three major routes: biliary tract, portal vein, and hepatic artery [9].…”
Section: Review Systemic Complication From Oral Bacterial Infectionmentioning
confidence: 99%
See 1 more Smart Citation